Modeling of the Beam-To-Column Dowel Connection for a Single-Story RC Precast Building - Magliulo, Gennaro; Di Salvatore, Chiara; Ercolino, Marianna (Frontiers in Built Environment, 2021)
As widely known, connections performance under seismic loads can significantly affect the structural response of RC precast buildings. Within the scientific community, an increasing number of studies has been carried out on this topic, in the light of the recent earthquake aftermaths all over Europe. Indeed, connections turned out to be the weakest part of the precast structures and their failure often provoked the global collapse of the whole building. The present study aims at assessing the seismic behavior of a single-story RC precast building in terms of global collapse implementing two different model of the beam-to-column connection, a simplified and a refined one. A lumped plasticity approach is used to simulate the structural nonlinear behavior at the column base. In order to assess the refined connection model, a preliminary scheme with an isolated single dowel is validated by comparing the pushover outcomes with experimental results from literature. Nonlinear static and dynamic analyses are performed on two models of a 3D single-story RC precast building, one implementing the simple beam-to-column connection model, the other one implementing the refined mode. The comparison clearly shows that the differences are negligible if the global collapse limit state is considered.